Fabrication and spectroscopic characterization of graphene transparent electrodes on flexible cyclo-olefin substrates for terahertz electro-optic applications. (23rd June 2020) - D'Arco, Annalisa; Mussi, Valentina; Petrov, Stefan; Tofani, Silvia; Petrarca, Massimo; Beccherelli, Romeo; Dimitrov, Dimitre; Marinova, Vera; Lupi, Stefano; Zografopoulos, Dimitrios C
Abstract: We demonstrate graphene on flexible, low-loss, cyclo-olefin polymer films as transparent electrodes for terahertz electro-optic devices and applications. Graphene was grown by chemical vapor deposition and transferred to cyclo-olefin polymer substrates by the thermal release tape method as layers on an approximate area of 4 cm 2 . The structural and electromagnetic properties of the graphene samples as well as their spatial variation were systematically mapped by means of µ Raman, terahertz time-domain and mid-infrared spectroscopy. Thanks to the small thickness and very low intrinsic absorption of the employed substrates, both high transmittance and conductivity were recorded, demonstrating the suitability of the technique for the fabrication of a new class of transparent and flexible electrodes working in the terahertz spectrum.